Amino acid and mineral composition of milk from local Ukrainian cows and their crossbreedings with Brown Swiss and Montbeliarde breeds - Borshch, A. A.; Borshch, A.V.; Lutsenko, M.M.; Merzlov, S.V.; Kosior, L.T.; Lastovska, I.A.; Pirova, L.V. (Diponegoro University, 2018)
The aim of this study was to analyze the mineral composition of milk, the amino acid composition of milk protein, and the productivity per 305 days of lactation in crossbred cows compared to pure-breed local Ukrainian analogues. The research was conducted at cows of the Ukrainian Black-Spotted (UBS) dairy breed and crossbred cows of the first-generation obtained as a result of crossing with Brown Swiss breed and at cows of the Ukrainian Red-Spotted (URS) dairy breed and crossbred cows of the first-generation obtained by crossing of the URS dairy breed with Montbeliarde breed. In both farms there were two groups of pure-breed and crossbred cows-analogues. The mineral composition of milk and its technological properties in crossbred cows were higher compared to the pure-breed analogues. The fat content of milk crossbred cows exceeded by 0.08-0.16%, protein exceeded by 0.15-0.22%, and the main trace elements include Ca and P – by 2.66-8.83 and 2.12-7.81 mg/100 g of milk, respectively. Milk protein of crossbred cows was marked by a more balanced composition of essential amino acids (EAAs) and their ratio suitable for processing. The amount of EAAs in 100 g of milk protein of crossbred cows was 3.11-6.25% higher compared to local analogues. Crossbred cows dominated pure-breed analogues by the mineral composition of milk. The authors recommend the use of Montbeliarde or Brown Swiss breeds in commercial herds to improve the technological properties of milk.